2002
DOI: 10.1161/01.res.0000040420.17366.2e
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9 Is Necessary for the Regulation of Smooth Muscle Cell Replication and Migration After Arterial Injury

Abstract: Abstract-Matrix metalloproteinases (MMPs) and, in particular, MMP-9 are important for smooth muscle cell (SMC) migration into the intima. In this study, we sought to determine whether MMP-9 is critical for SMC migration and for the formation of a neointima by using mice in which the gene was deleted (MMP-9 Ϫ/Ϫ mice). A denuding injury to the arteries of wild-type mice promoted the migration of medial SMCs into the neointima at 6 days, and a large neointimal lesion was observed after 28 days. In wild-type art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
254
2
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(278 citation statements)
references
References 35 publications
14
254
2
8
Order By: Relevance
“…Cho and Reidy (2002) have demonstrated in mice lacking the MMP-9 gene that MMP-9 is critical for VSMC migration and the formation of neointima. Diabetes mellitus has been identified as an independent risk factor for the development of atherosclerosis and is considered a coronary-heart-disease risk equivalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho and Reidy (2002) have demonstrated in mice lacking the MMP-9 gene that MMP-9 is critical for VSMC migration and the formation of neointima. Diabetes mellitus has been identified as an independent risk factor for the development of atherosclerosis and is considered a coronary-heart-disease risk equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…VSMC migration, which depends on an alteration of the proteolytic balance within the arterial wall toward matrix breakdown, is partly mediated by matrix metalloproteinases (MMPs). MMP-9 is indispensable for the degradation of type IV collagen, a major component of the basement membrane (Zucker et al, 1993;Cho and Reidy, 2002). Recent experimental data have shown that hyperglycemic diabetes can induce altered expression of the genes encoding MMP-9 (Death et al, 2003) and plasma levels and zymographic activities of MMP-9 are increased in diabetics with peripheral arterial disease as compared with non-diabetics (Signorelli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages, depending on their origin and state of activation, express several members of the MMP family including MMP-9 (23, 24). As observed for the uPA/plasminogen system, several studies have suggested a role for MMP-9 in cell migration, and leukocyte infiltration and tissue remodeling are reduced in MMP-9 null mice (20,(25)(26)(27)(28)(29).Because of their role in migration and/or tissue remodeling, the regulation of uPA and MMP-9 expression in macrophages has received much attention. The expression of both proteinases, as well as their specific inhibitors, is regulated by cytokines and growth factors (30 -32).…”
mentioning
confidence: 98%
“…Macrophages, depending on their origin and state of activation, express several members of the MMP family including MMP-9 (23,24). As observed for the uPA/plasminogen system, several studies have suggested a role for MMP-9 in cell migration, and leukocyte infiltration and tissue remodeling are reduced in MMP-9 null mice (20,(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Thinning of the fibrous cap by MMPs is undesirable due to the release of sequestered factors that leads to thrombosis [15]. TNF-α regulation of MMP-9 is of particular importance in atherosclerotic lesion development and in fibrous cap thinning [3,20]. Thus, up-regulation of MMP-9 expression by TNF-α can promote development of atherosclerotic lesions by multiple mechanisms that include stimulation of SMC proliferation and MMP-9 production.…”
mentioning
confidence: 99%